PENGARUH FLYPAPER EFFECT TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH PROVINSI/KABUPATEN/KOTA SE-BALI DAN JAWA TAHUN 2019-2021 - Putu Dany Indrawan Sidhi; Nyoman Ayu Wulan Trisna Dewi (Vokasi : Jurnal Riset Akuntansi, 2023)
This study aims to analyze the phenomenon of the flypaper effect on the financial performance of provinces/districts/cities throughout Bali and Java in 2019-2021. This study used two regression data tests, namely multiple linear regression and simple linear regression. The sample selection was carried out using purposive sampling method in order to obtain a total sample of 126 local governments. The results of the study found that 1) the General Allocation Fund (DAU) has a significant effect on capital expenditures; 2) Special Allocation Funds have no significant effect on capital expenditures; 3) Profit Sharing Fund (DBH) has no significant effect on capital expenditure; 4) Regional Original Income (PAD) has no significant effect on capital expenditure; 5) The coefficient of DAU on capital expenditure is greater than PAD on capital expenditure, which means that there has been a flypaper effect; 6) Flypaper effect has no significant effect on financial performance. Based on this condition, it is hoped that local governments will continue to maximize the role of PAD in conducting regional expenditures so that there is no dependence on balancing funds.